Transforming Interprofessional Partnerships : a New Framework for Nursing and Partnership-Based Health Care - Eisler, Riane Tennenhaus; Potter, Teddie M., 1956- (Sigma Theta Tau International, 2014)
Transforming Interprofessional Partnerships: A New Framework for Nursing and Partnership-Based Health Care provides nurses and other health care professionals tools to reexamine the current state of interdisciplinary partnerships in order to build a more effective, caring, and sustainable health care system. This comprehensive text will benefit nurses by defining and illustrating full partnership in practice, education, and research in order to improve communication and interprofessional collaboration.